Effect financial competence in investment decisions: a case study in the light of the Prospectus Theory - Tashiro, Giullia Manli Higashi; Capelato, Erika (Departamento de Economia, 2018)
The Prospect Theory, by Kahneman and Tversky, points out that individuals have limitations in fully exercising their rationality in decision-making processes reacting differently to the same problem when it is presented in different ways. Thus using the Prospect Theory as a theoretical basis this article discussed and analyzed if it has some previous knowledge in finance can influence the formation of decision processes in investment situations. For this we replicate the empirical investigation of the seminal article by Kahneman and Tversky (1979) to two groups of students with distinct competences in finance and the results indicated, as in seminal research, that there are cognitive biases in the two groups, There is the presence of certainty effects, reflection and isolation, which oppose the hypotheses of the Expected Utility Theory.